频谱函数F(jω)=2u(1−ω)的傅里叶逆变换f(t)= _____。
A: [img=86x39]18034ef63cec38f.png[/img]
B: [img=91x41]18034ef64532a69.png[/img]
C: [img=92x41]18034ef64dc2d20.png[/img]
D: [img=98x39]18034ef65702c7b.png[/img]
A: [img=86x39]18034ef63cec38f.png[/img]
B: [img=91x41]18034ef64532a69.png[/img]
C: [img=92x41]18034ef64dc2d20.png[/img]
D: [img=98x39]18034ef65702c7b.png[/img]
举一反三
- 设函数f(x)可微,则d(ef(x))=( )。 未知类型:{'options': ['', ' [img=51x21]17e0bc860be5938.png[/img]', ' [img=83x24]17e0bc86176d413.png[/img]', ' [img=89x24]17e0bc8622ae5f2.png[/img]'], 'type': 102}
- 设f(x)可微,则d(ef(x))=()。 A: f,(x)dx B: ef(x)dx C: f,(x)ef(x)dx D: ef,(x)dx
- 设函数y=f(ex)ef(x),其中f(x)可导,则dy=()。 A: ef(x)[exf'(x)+f'(ex)]dx B: ef(x)[exf'(ex)+f(ex)f'(x)]dx C: ef(x)[f'(ex)+f(ex)f'(x)]dx D: ef(x)[f'(ex)+exf(ex)f'(x)]dx
- 频谱函数[img=244x25]18031110f2db411.png[/img]的傅里叶逆变换x(t)为( )。 A: [img=157x69]18031110fda2782.jpg[/img] B: [img=159x82]18031111090dfb9.jpg[/img] C: [img=158x36]18031111141c0eb.jpg[/img] D: [img=166x82]180311111f8fb64.jpg[/img]
- 频谱函数[img=244x25]180311139a40e03.png[/img]的傅里叶逆变换x(t)为( )。 A: [img=157x69]18031113a5a9ec2.jpg[/img] B: [img=159x82]18031113b086efd.jpg[/img] C: [img=158x36]18031113bb1c88e.jpg[/img] D: [img=166x82]18031113c612a4b.jpg[/img]